Mutational diversity and therapy response in breast cancer - a sequencing analysis in the neoadjuvant GeparSepto trial - Loibl, Sibylle; Treue, Denise; Budczies, Jan; Weber, Karsten; Stenzinger, Albrecht; Schmitt, Wolfgang D.; Weichert, Wilko; Jank, Paul; Furlanetto, Jenny; Klauschen, Frederick; Karn, Thomas; Pfarr, Nicole; et al. (Clinical cancer research, 2019)
Purpose: Next-generation-sequencing (NGS) can be used for comprehensive investigation of molecular events in breast cancer (BC). We evaluated the relevance of genomic alterations for response to neoadjuvant chemotherapy (NACT) in the GeparSepto trial. Experimental Design: 851 pretherapeutic FFPE core biopsies from GeparSepto study were sequenced. The panel included 16 genes for mutational (AKT1, BRAF, CDH1, EGFR, ERBB2, ESR1, FBXW7, FGFR2, HRAS, KRAS, NRAS, SF3B1, TP53, HNF1A, PIK3CA, PTEN) and 8 genes for copy number alteration analysis (CCND1, ERBB2, FGFR1, PAK1, PIK3CA, TOP2A, TP53, ZNF703). Results: The most common genomic alterations were mutations of TP53 (38.4%) and PIK3CA (21.5%), and 8 different amplifications (TOP2A 34.9%; ERBB2 30.6%; ZNF703 30.1%; TP53 21.9%; PIK3CA 24.1%; CCND1 17.7%; PAK1 14.9%; FGFR 12.6%). All other alterations had a prevalence of less than 5%. The genetic heterogeneity in different BC subtypes (lum/HER2neg vs HER2pos vs TNBC) was significantly linked to differences in NACT response. A significantly reduced pCR rate was observed in PIK3CA-mutated BC (PIK3CAmut: 23.0% vs wildtype (wt) 38.8%, p<0.0001) in particular in the Her2pos subcohort (multivariate OR=0.43 [0.24-0.79], p=0.006). An increased response to nab-paclitaxel was observed only in PIK3CAwt BC, with univariate significance for the complete cohort (p=0.009) and the TNBC (p=0.013) and multivariate significance in the HER2pos subcohort (test for interaction p=0.0074). Conclusions: High genetic heterogeneity was observed in different BC subtypes. Our study shows that FFPE-based NGS can be used to identify markers of therapy resistance in clinical study cohorts. PIK3CA mutations could be a major mediator of therapy resistance in BC.